Resolution of Consumer Personal Data Protection Efforts during Online Buying and Selling Transactions - Bonaraja Purba; Grace Ambarita; Lastiara Manik; Nopia Simamora (Indonesian Journal of Advanced Research, 2023)
The purpose of this study is to discuss resolutions regarding the protection of consumers' personal data when buying and selling online. The research method used in this research is data collection through library research, collected through literature research, namely by studying the provisions of the law regarding online/e-commerce transactions and other laws and regulations that are relevant to the research material. The results of the study show that in general Indonesia has legal regulations governing privacy policy in E-Commerce, which are contained in Law Number 11 of 2008 concerning Electronic Information and Transactions (UU Nomor 18 Tahun 2008 tentang ITE) and Government Regulation Number 28 of 2012 concerning Implementation of Electronic Systems and Transactions (PP Nomor 28 Tahun 2012 tentang PSTE). This is intended so that consumers avoid or can prevent fraud by irresponsible persons.